2017
DOI: 10.3389/fpsyg.2017.01984
|View full text |Cite
|
Sign up to set email alerts
|

On the Interpretation and Use of Mediation: Multiple Perspectives on Mediation Analysis

Abstract: Mediation analysis has become a very popular approach in psychology, and it is one that is associated with multiple perspectives that are often at odds, often implicitly. Explicitly discussing these perspectives and their motivations, advantages, and disadvantages can help to provide clarity to conversations and research regarding the use and refinement of mediation models. We discuss five such pairs of perspectives on mediation analysis, their associated advantages and disadvantages, and their implications: w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
200
2
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(211 citation statements)
references
References 48 publications
4
200
2
5
Order By: Relevance
“…Moreover, results were consistent with a mediation model - the indirect effect of age on the ERN via social anxiety symptoms was significant, effect = −.03, 95%CI[−.09, −.01], suggesting that developmental increases in social anxiety symptoms as reported by parents underlies, in part, the developmental increase in the ERN. To test specificity of the model, the mediator and outcome were reversed (i.e., social anxiety symptoms were entered as the outcome variable and the ERN was entered as the mediator; Agler & De Boeck, 2017). Results suggested that the indirect path did not reach significance, effect = .005, 95%CI[−.02, .09].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, results were consistent with a mediation model - the indirect effect of age on the ERN via social anxiety symptoms was significant, effect = −.03, 95%CI[−.09, −.01], suggesting that developmental increases in social anxiety symptoms as reported by parents underlies, in part, the developmental increase in the ERN. To test specificity of the model, the mediator and outcome were reversed (i.e., social anxiety symptoms were entered as the outcome variable and the ERN was entered as the mediator; Agler & De Boeck, 2017). Results suggested that the indirect path did not reach significance, effect = .005, 95%CI[−.02, .09].…”
Section: Resultsmentioning
confidence: 99%
“…The indirect effect of poor oral health on increased frailty index through the pathway of increasing poor diet scale was found for increasing number of oral health problem categories. The proportion of the indirect effect to the direct effect was calculated as the proportion explained by the path …”
Section: Methodsmentioning
confidence: 97%
“…The process of examination highlighted the mediation analysis of microfinancing on the effect of access to finance on the growth of microenterprises. The objective of the mediation analysis was to seek a deeper understanding of the direct and indirect effects of the independent variable (IV) on the dependent variable (DV) when there is a mediator variable (Agler & De Boeck, 2017). Since the study is about the impact on growth, the process was expected to change the level of the effect as a result of the mediating variable; thus, the total effect of IV on DV in a normal regression may be found insignificant when mediation analysis is applied.…”
Section: Methodsmentioning
confidence: 99%